Function in context: Why American and Trinidadian young and older adults remember the personal past - Alea, Nicole (Memory, 2014)
Multiple and interacting contextual (culture, life phase) and person-specific predictors (i.e., personality, tendency to think-talk about the past) of the functions of autobiographical memory were examined using the Thinking about Life Experiences scale. American (N = 174) and Trinidadian (N = 182) young and older adults self-reported how frequently they remembered the personal past to serve self, social, and directive functions, how often they thought and talked about their past overall, and completed a measure of trait personality. Independent contextual and person-specific predictors were found for using memory to serve a social-bonding function: Americans, young adults, those higher in extraversion, lower in conscientiousness, and individuals who frequently think and talk about the past more often use autobiographical memory for social-bonding. Across cultures, younger adults report more frequently using memory to serve all three functions, whereas Trinidadians who think more often about the past compared with those who reflect less often, are more likely to use it for self and directive functions. Findings are discussed in terms of the individual’s embeddedness in cultural and life phase contexts when remembering.